Evaluation of sliding mode and proportional-integral-derivative controlled structures with an active mass damper - Guclu, R; Sertbas, A (SAGE PUBLICATIONS LTD, 2005)
In this paper, both a sliding mode controller (SMC) and proportional-integral-derivative (PID) controller are designed for a multi-degrees-of-freedom structure, which has an active mass damper (AMD) to suppress earthquake- or wind-induced vibration. Since the model might have uncertainties and/or parameter changes, a SMC has been included because of its robust character and performance. The structural system has five degrees of freedom and has been simulated against an initial displacement of the first floor. At the end of the paper, we present the time histories of the first floor, top floor, and AMD displacements, the control voltage and frequency response of the uncontrolled, PID controlled, and sliding mode controlled structures, and we discuss the results.
Keywords: sliding mode control; active mass damper; structure; vibration; Acoustics; Engineering; Mechanics